Giant Hypertrophy of the Fifth Cervical Spinous Process with associated Hemivertebra presenting as Posterior Neck Mass - Emeka, Obirija Samson; Mumuni Wemimo, Rasheed (The Nigerian Health Journal, 2024)
Congenital anomalies of the spine are relatively common and can affect both upper and lower limbs. However, hypertrophy of the spinous process is an extremely rare anomaly of the cervical spine, and many anomalies of the cervical spines are commonly encountered which include persisting apophyses of the transverse processes, persisting epiphyses, vertebral platyspondylia, vertebral hypoplasia, and dysplasia of the arch of the vertebra. The majority of these vertebral abnormalities are often incidental findings in radiography with few causing pain, and aesthetic problems to the patients. Thus, we present a 12-year-old female who presented to the paediatric outpatient clinic on account of swelling at the lower back of her neck of 4 years duration, and recurrent neck pain of one-month duration. The patient noticed the mass 4- years prior to presentation, as a painless, slow-growing lump behind her neck which appears more prominent whenever she flexes her neck. The USS revealed a linear hyperechogenicity within the hypoechoic soft tissue (muscle) of the posterior neck and a plain radiograph of the neck was subsequently obtained and showed abnormal elongation with downward curvature of the spinous process of the sixth cervical vertebra. A diagnosis of giant hypertrophy of the fifth cervical vertebra spinous process with hemivertebra at C6 was made. The was managed conservatively with satisfactory outcomes.